Development and In-Vitro Evaluation of pH Responsive Polymeric Nano Hydrogel Carrier System for Gastro-Protective Delivery of Naproxen Sodium - Rai Muhammad Sarfraz; Muhammad Rouf Akram; Muhammad Rizwan Ali; Asif Mahmood; Muhammad Usman Khan; Husnain Ahmad; Muhammad Naeem Qaisar (Advances in Polymer Technology)
Current research work was carried out for gastro-protective delivery of naproxen sodium. Polyethylene glycol-g-poly (methacrylic acid) nanogels was developed through free radical polymerization technique. Formulation was characterized for swelling behaviour, entrapment efficiency, Fourier transform infrared (FTIR) spectroscopy, Differential scanning calorimetry (DSC), and Thermal Gravimetric Analysis (TGA), Powder X-ray diffraction (PXRD), Zeta size distribution, and Zeta potential measurements, and in-vitro drug release. pH dependent swelling was observed with maximum drug release at higher pH. PXRD studies confirmed the conversion of loaded drug from crystalline to amorphous form while Zeta size measurement showed size reduction. On the basis of these results it was concluded that prepared nanogels proved an effective tool for gastro-protective delivery of naproxen sodium.